Respuesta :
Answer:
B. the addition property of equality
Step-by-step explanation:
we have:
Step 1: 7x − 25= 4x − 1
we apply the addition property of equality:
7x − 25+25= 4x − 1 +25
finally we have
Step 2: 7x = 4x + 24
Answer: OPTION B.
Step-by-step explanation:
Given the following equation:
[tex]10x - 25 - 3x = 4x- 1[/tex]
These are the steps to solve it:
Step 1
Add like terms on the left side of the equation:
[tex]7x -25= 4x - 1[/tex]
Step 2
Apply Addition property of equality, which states that: [tex]If\ a=b\ then\ a+c=b+c[/tex]
Then, we can add 25 to both sides of the equation:
[tex]7x -25+(25)= 4x - 1+(25)\\\\7x=4x+24[/tex]
Step 3
Applying the Subtraction property of equality, we can subtract [tex]4x[/tex] from both sides:
[tex]7x-4x=4x+24-(4x)\\\\3x=24[/tex]
Step 4
Applying the Division property of equality, we can both sides of the equation by 3. Then:
[tex]\frac{3x}{3}=\frac{24}{3}\\\\x=8[/tex]